THE PROBABILITY DETERMINATION OF ERROR-FREE AIR TRAFFIC CONTROLLER OPERATION - V. E. Borisov; V. V. Borsoeva; S. M. Stepanov; A. I. Stepnova (Научный вестник МГТУ ГА)
Human error is considered to be a cause or one of the main factors in most accidents. Errors are not a certain type of deviation in behaviour; they are a natural product of all human efforts. Errors must be accepted as a normal component of any system, in which humans and technology interact. In aviation for decades since 1960-ies the share of the human factor (HF) from the total number of aviation accident reasons is estimated by the constant growth from 40–50 to 80–90% [1]. This figure refers generally to the certified flight personnel of commercial aviation. Taking into account flights of General aviation (GA), maintenance, air traffic control, transport infrastructure, the overall share of the HF is over 90%. The subject content of HF focuses on the study of man in various conditions and relations to natural habitat and anthropogenic activities. The HF concept is aimed at finding the reasons for unsatisfactory activity and is understood as a field of methods development to optimize safety. In the understanding of human activities inaccuracy is the history of feelings and ideas about responsibility and free will. Erroneous human actions are the result of many simultaneous and asynchronous processes of air transport subjects and the social environment. The study of the nature of erroneous actions leads to conclusions about the deep origin in the human mentality structures of intentions, opinions and expression of the will. Consequence evaluation takes place during changing environment and individual consciousness. The results are often perceived as not corresponding to the original intentions. The human factor acquires special relevance at introduction of the navigation based on characteristics (PBN). Airline companies and services of Air Traffic Control (ATC) face serious problems while implementing the international standards on human factor.